Molecular detection and sequencing of beet necrotic yellow vein virus and beet cryptic virus 2 in sugar beet from Kazakhstan - Pozharskiy, Alexandr; Mendybayeva, Aruzhan; Moisseyev, Ruslan; Khusnitdinova, Marina; Nizamdinova, Gulnaz; Gritsenko, Dilyara (Frontiers in Microbiology, 2024)
IntroductionBeet necrotic yellow vein virus (BNYVV) is a common viral pathogen that causes considerable economic loss globally. In the present study, a commercial realtime PCR test system and custom loop mediated amplification primers were used to detect the virus in asymptomatic sugar beet samples.MethodsA total of 107 of 124 samples tested positive for the presence of the A type BNYVV coat protein gene. Near complete sequences of RNA-3 and RNA-4 were obtained using reverse transcription, followed by nanopore sequencing of 14 samples.Results and discussionA comparison with available sequences, including previously published isolates Kas2 and Kas3 from Kazakhstan, identified RNA-3 as similar to such of the P-type isolates Puthiviers and Kas3. RNA-5 was not detected using real-time PCR or cDNA amplification. Unique variable sites were identified in the p25 protein sequence translated from RNA-3. Another virus, beet cryptic virus 2 (BCV2), was identified and sequenced in samples infected with BNYVV. With 85.28% genome coverage, the identified BCV2 samples were very similar to the previously reported isolates from Hungary and Germany